METAPLASMOS E O ENSINO DE ORTOGRAFIA: UMA PROPOSTA DIDÁTICA PARA O ESTUDO DE VERBOS NO INFINITIVO - GARCIA, BRUNA TARGINO DIAS (2022)
This paper aimed to analyze textual productions of 9th grade students in order to verify which metaplasm occurred more frequently in their texts. The metaplasm that appeared more often was apocopy, specifically the apocopy of /R/ in infinitive verbs. Therefore, we aimed to develop a didactic proposal (DOLZ et al., 2022) about the study of verbs in the infinitive. For this, this research was based on Botelho (2013), Botelho e Leite (s/d), Bagno (2007; 2011; 2012), Messias (2017) and Monaretto (2000) for the study around metaplasms and the occurrence of apocopy, and on Roberto (2016), Morais (2010), Haupt (2012), the PCN (BRASIL, 1998) and the BNCC (BRASIL, 2017), aiming at the elaboration of a didactic sequence based on reflection about usage. Furthermore, a questionnaire was also applied to the same class in which the textual productions analyzed in this study were developed. It aimed to collaborate with the research about teaching and to contribute to the construction of the didactic proposal. The results of this application are analyzed in this paper.